ONLINE LEARNING READINESS LEVEL OF FIRST AND SECOND YEAR STUDENTS AT FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, VNU UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES - Viet, Khoa Anh; Linh, Nguyen Khanh (VNU Journal of Foreign Studies; Vol 37 No 6DO - 10.25073/2525-2445/vnufs.4430, 2021)
Recent advances in Information and Technology Communication (ICT) have prompted significant changes in the domain of education, particularly in the rise of online learning. In early 2018, VNU University of Languages and International Studies (VNU-ULIS) started implementing several web-based courses on a Learning Management System (LMS), in an attempt to encourage the development of online learning at the university. The aim of this study was to investigate the level of readiness for online learning of potential learners of LMS so that both course instructors and course participants would be able to identify difficulties that they might encounter in the novel virtual teaching and learning environment. The data collection process was divided into two phases: closed-ended questionnaire and semi-structured interviews afterwards. The main instrument was Online Learning Readiness Scale developed by Hung Chou, Chen and Own (2010).The final results indicated that university students from both academic years get relatively high levels of online readiness, yet the second year student participants had a slightly higher level of readiness than the first year participants. Therefore, the implementation of LMS was probably more suitable for sophomore ones.